Approaches and Methods in Language Teaching and Learning over Time - Khaled Jebahi (Language and Literacy: A Canadian Educational e-journal, 2022)
This study is an attempt to review the main language teaching approaches and methods used in the last hundred and fifty years or so. This is justified by the fact that though some teachers, native and non-native, may have some knowledge of the theoretical underpinnings of their classroom practices and techniques, they may lack an understanding of some other related past and present teaching methods and approaches. Those methods and approaches are reviewed in a simple and straightforward fashion. The theoretical, economic, political, and educational factors affecting their development, implementation, and change are touched upon in order for teachers to better understand their classroom implementation and seek to improve it and justify it with reference to a clearer, simpler, and more straightforward reading of the literature on the topic in focus.